PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN SYARIAH (ISLAMIC SOCIAL REPORTING) - Fitri Selvia; Lela Nurlaela Wati; Bono Prambudi (STIE Muhammadiyah Jakarta, 2020)
The concept of corporate social responsibility (CSR) is now not only developing conventional economics, but also in the Islamic economy. The concept of CSR in Islam is Islamic Social Reporting, which is a special framework for reporting social responsibility in accordance with Islamic principles. The framework is not only useful for Muslim decision makers, but also useful for helping Islamic companies in fulfilling obligations towards Allah SWT and society. This writing method used literature review through various literature with the aim of informing the reader (informative research) about the themes in social responsibility disclosure in sharia-based companies.